Learners’ Motivation in Learning English Vocabulary Using Direct Method - Saiful, Saiful (Edumaspul: Jurnal Pendidikan, 2023)
The study’s aimed at determining the motivation of students with regards to studying English as a Foreign Language using Direct Methods. The study population includes the ninth grade students at SMPN 3 Mare academic year 2022/2023 with 19 respondents. This study is descriptive research, and as a result of this analysis the researcher has identified an improvement in student motivation affecting active behavior and emotion associated with passion for vocabulary learning. It can be concluded, based on the results of the study, that there is a gain in motivation for pupils to learn words by indirect methods.